2018
DOI: 10.5194/acp-18-601-2018
|View full text |Cite
|
Sign up to set email alerts
|

A refined method for calculating equivalent effective stratospheric chlorine

Abstract: Abstract. Chlorine and bromine atoms lead to catalytic depletion of ozone in the stratosphere. Therefore the use and production of ozone-depleting substances (ODSs) containing chlorine and bromine is regulated by the Montreal Protocol to protect the ozone layer. Equivalent effective stratospheric chlorine (EESC) has been adopted as an appropriate metric to describe the combined effects of chlorine and bromine released from halocarbons on stratospheric ozone. Here we revisit the concept of calculating EESC. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 44 publications
4
46
3
Order By: Relevance
“…The fractional release factor and global lifetime for CFC-11 were taken from the WMO (2014) ozone assessment report to be 0.47 and 52 years, respectively. Note that a new method to calculate FRF has been suggested by Ostermöller et al (2017a, b), which has been applied by Leedham Elvdige et al (2018) and Engel et al (2018). Overall, there is good agreement between the new method and the empirical parameterization applied in this work.…”
Section: Ozone Depletion Potentials (Odps)supporting
confidence: 65%
“…The fractional release factor and global lifetime for CFC-11 were taken from the WMO (2014) ozone assessment report to be 0.47 and 52 years, respectively. Note that a new method to calculate FRF has been suggested by Ostermöller et al (2017a, b), which has been applied by Leedham Elvdige et al (2018) and Engel et al (2018). Overall, there is good agreement between the new method and the empirical parameterization applied in this work.…”
Section: Ozone Depletion Potentials (Odps)supporting
confidence: 65%
“…EESC values are presented in Table 3 for historical and future chemistry-climate scenarios. In all cases, EESC compuations were informed by the time-independent fractional release factors provided in Table 1 of Engel et al (2018). These EESC calculations are visualized in Figure 5.…”
Section: Future Eescmentioning
confidence: 99%
“…This quantity expresses the ozone-depleting power of a parcel of well-mixed stratospheric trace gases as a function of mean stratospheric age of the parcel, Γ, and the trace gas background of the stratosphere at time t (Daniel et al, 1995;Newman et al, 2007). Equation 3 provides the most recently suggested formulation of EESC, in which f i (Γ) is the time-independent fractional release factor for species i for a parcel of air with mean age Γ, which contains n i,Cl chlorine atoms and n i,Br bromine atoms, scaled by α Br (t, Γ), where it is assumed that Γ can serve as a proxy for ρ (Ostermöller et al, 2017;Engel et al, 2018). Inside the integral, the mixing ratio of species i is computed for each element comprising the age spectrum and normalized to the contribution of that element to the age spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While stratospheric ozone recovery from the slow removal of inorganic chlorine from the stratosphere is expected to occur within this century driven largely by a decrease in ozone depleting substances (Austin et al, 2010;Chipperfield et al, 2017;Li et al, 2009;Oman & Douglass, 2014;Steinbrecht et al, 2018;Stone et al, 2018;World Meteorological Organization, 2014) due to the Montreal Protocol, recent modeling and observational studies show that additional halogen sources could slow this recovery (Engel et al, 2018;Hossaini et al, 2016;Yang et al, 2014). In particular, convectively transported halogenated very short lived substances of chlorine (Hossaini, Chipperfield, Montzka, et al, 2015;Hossaini, Chipperfield, Saiz-Lopez, et al, 2015;Hossaini et al, 2017;Laube et al, 2008;Oram et al, 2017), bromine (Aschmann et al, 2009;Dessens et al, 2009;Hossaini, Chipperfield, Montzka, et al, 2015;Liang et al, 2014;Salawitch et al, 2005;Wales et al, 2018;Yang et al, 2014), and iodine (Hossaini, Chipperfield, Saiz-Lopez, et al, 2015;Saiz-Lopez et al, 2015;Youn et al, 2010) have been shown to be important sources of stratospheric halogens.…”
Section: Introductionmentioning
confidence: 99%